Terrestrial Slugs in Neotropical Agroecosystems - Ramos, Mariangie; Gomes, Suzete Rodrigues; Gutierrez, Yashira; Ramos-Rodriguez, Olgaly; Uzeda, Mariella Carmadelli (Frontiers in Sustainable Food Systems, 2021)
Slugs can be important agricultural pests in tropical regions. They are also intermediate hosts of parasitic nematodes, such as Angiostrongylus costaricensis and A. cantonensis, which can cause abdominal and cerebral angiostrongyliasis in humans. Management of slugs in conventional agriculture has relied heavily in the use of pellets containing metaldehyde. In this article, we review cases of slug problems and their management in neotropical agroecosystems.